3D analysis of facial morphology in Dutch children with cancer. (June 2021) - Postema, Floor A.M.; Matthews, Harold; Hopman, Saskia M.J.; Merks, Johannes H.M.; Suttie, Michael; Hoskens, Hanne; Peeters, Hilde; Hennekam, Raoul C.; Claes, Peter; Hammond, Peter
Highlights: Genetic risk factors for childhood cancer may also influence facial morphology. 3D facial photography can be used to identify facial asymmetry and facial signature. The faces of children with cancer are not more asymmetric compared to controls. The faces of children with cancer deviate more from average than controls. ABSTRACT: Background and Objective; Genetic risk factors for childhood cancer may also influence facial morphology. 3D photography can be used in the recognition of differences in face shape among individuals. In previous research, 3D facial photography was used to identify increased facial asymmetry and greater deviation from normal facial morphology in a group of individuals with distinct morphological features who had childhood cancer compared to healthy controls. In this study, we aim to determine whether there is a difference in facial morphology between children with cancer without previously selected morphological features and healthy controls, detected with 3D facial photography. Methods: Facial 3D photographic images were obtained of children with a newly diagnosed malignancy. The resulting sample comprised 13 different cancer types. Patients were excluded if they had a known genetic cause of the cancer. Patients were compared to healthy controls, matched for sex, age and ethnic background. The degree of asymmetry and overall deviation of an individual's face from an age and sex typical control face were measured. Results: A total of 163 patients of European descent were included. No significant difference in asymmetry between patients and controls could be identified. On average, patients deviated more from an age and sex typical face than the controls. Conclusion: This study shows that children with cancer deviate more than controls, possibly suggesting a higher prevalence of genetic anomalies within this group. The results suggest that this is not sufficient to discriminate patients from controls. Further research is necessary to explore the patterns of individual variation among the overall deviation of patients and controls.